The implications of lah, ah, and hah as used by some speakers in Malaysia - Ching Hei Kuang (Journal of Modern Languages)
This study looks at two groups of ethnic Malaysians, Malays and Chinese, in the way they perform their oral interactions, whether through Chinese (Mandarin or Hokkien) or Malay, particularly in the manner their intentions, desires, or emotions were demonstrated via the use of Malaysian discourse markers or particles. Data collected and analysed in this study suggests that specific Malaysian discourse markers or particles, whether tagged at the beginning, in the middle or at the end of utterances, carry specific connotations as a result of mother tongue or Ll influences. For the purpose of analysing data collected in this study, I will attempt to construct a hypothesis for the use of the Malaysian particles of lah (la), and ah (aaa) by adopting some of Lee's (1995) comments while the analysis of the hah particle is my own.